Conceptual Design of Diagrids and Hexagrids by Distribution of Lattice Structures - Bruggi, Matteo (Frontiers in Built Environment, 2020)
The conceptual design of grid systems in tall buildings is addressed combining optimization and multiscale analysis of lattice structures. Macroscopic properties of lattices with given cross-section are available in the literature for different cell topologies. A multi-material optimization problem is formulated to find the distribution of a prescribed discrete set of candidate cross-sections and shapes such that the structural weight of the grid is minimized under constraints on the lateral displacements of the building. Preliminary numerical simulations are shown addressing the design of tall buildings that employ diagrids and hexagrids.